Management of a complete denture in the flat mandibular ridge using a semi-adjustable articulator along with an effective suction method - Muhammad Dimas Aditya Ari; Harry Laksono; Valerian Laksono; Real Akbar Aucky Sanjaya; Tasya Regita Pramesti; Ratri Maya Sitalaksmi (Dental Journal, 2022)
Background: Complete dentures can improve the quality of life of edentulous patients. The selection of a suitable articulator and an impression technique is important to construct a stable and retentive complete denture with good occlusion. The use of a semiadjustable articulator ensures that the dentures can be constructed such that their movement closely resembles the patient’s physiological movements. The effective suction method can ensure the development of the border seal according to the patient’s anatomical condition. The use of a semi-adjustable articulator along with an effective suction method is expected to provide good results in the construction of a complete denture. Purpose: This report aimed to describe the management of individual complete dentures in the flat mandibular ridge using a semi-adjustable articulator along with an effective suction method. Case: A 69-year-old female patient came with a chief complaint of her old dentures being unusable and wanted new dentures made. The patient’s general condition was good, and the last extraction was done three months prior to the patient’s arrival. The mandibular posterior alveolar ridge showed dextral tapering and sinistral flatness. Case Management: A complete denture with an acrylic base was fabricated using a semi-adjustable articulator along with an effective suction method. Conclusion: Flat ridge case management using a semi-adjustable articulator with an effective suction method can improve complete denture retention and stability.